STRATEGI PERSONAL BRANDING GENERASI Z MELALUI MEDIA SOSIAL DALAM MEMBANGUN IDENTITAS PROFESIONAL DI ERA DIGITAL - Erwin Erwin; Putri Aulia; Afif Muhammad Dzaki (Jurnal Pengabdian Tangerang Selatan [JURANTAS], 2026)
The rapid advancement of information and communication technology has significantly transformed the way Generation Z communicates, accesses information, and develops professional competencies. Social media platforms are no longer used solely for entertainment but have evolved into strategic tools for self-development, professional networking, and personal branding. However, many students still lack the knowledge and skills required to utilize social media productively and responsibly. This Community Service Program aimed to improve the digital literacy and personal branding competencies of students at SMK Negeri 59 Jakarta through educational training on social media optimization and digital content strategies. A training method with a qualitative descriptive approach was employed using presentations, interactive discussions, observations, question-and-answer sessions, and practical content creation activities. The training materials covered digital literacy, personal branding, content creation strategies, social media optimization, and digital ethics. The results indicate that participants gained a better understanding of building a positive digital identity, developing creative and informative content, and utilizing social media as a platform for self-development, entrepreneurship, and career preparation. The program also increased participants' awareness of the importance of maintaining a professional digital footprint in today's digital era. It is expected that this activity will encourage Generation Z to become responsible, innovative, and competitive digital citizens capable of adapting to the challenges of the Industrial Revolution 4.0 and Society 5.0.